Prenatal Alcohol Exposure and Child Psychosocial Behavior: A Sibling Fixed-Effects Analysis - Ichikawa, Kayoko; Fujiwara, Takeo; Kawachi, Ichiro (Frontiers in Psychiatry, 2018)
Background: The association between low levels of alcohol consumption during pregnancy and children’s health remains unclear because of the difficulty in ruling out residual genetic and environmental confounding factors. In this study, using a within-family sibling fixed effects design, we sought to examine the association between low prenatal alcohol exposures (PAE) and children’s overall psychosocial behavior in a Japanese cohort. Methods: We used maternal and sibling data from the Japanese Study of Stratification, Health, Income and Neighborhood 2012-2013. Households were recruited from the Tokyo metropolitan area through clustered random sampling. Children under 18 years old who have siblings (n=1,600) and their mothers were selected. PAE status was retrospectively measured, and classified by binominal and continuous measurements. Outcome measures of children’s psychosocial behavior were assessed with the Child Behavior Checklist T-score. Results: Low PAE was significantly associated with the offspring’s anxiety problems (β=1.54, 95%CI=0.26, 2.82) and internalizing problems (β=2.73, 95%CI=0.87, 4.60), and marginally significant with the offspring’s total problem scores (β=2.34, 95%CI=-0.24, 4.92). There was no significant difference in PAE between boys and girls when it comes to behavioral problems. Conclusions: Low PAE was associated with children’s anxiety, internalizing problems and overall problems, taking into account possible unobserved genetic and environmental confounding influences.